ANALISIS KINERJA JALAN LUAR KOTA SAMARINDA - BALIKPAPAN PADA RUAS JALAN SOEKARNO-HATTA PADA KM. 17+000 - KM. 37+000 - BUDIARTO, MUHAMMAD RICO (KURVA S JURNAL MAHASISWA, 2014)
Muhammad Rico Budiarto , NPM : 10.11.1001.7311. 019 , the Outer Path Performance Analysis of Samarinda Balikpapan On Roads Soekarno Hatta At Kilometer 17 to 37 kilometers, Supervisor I : Rossa Agustaniah, ST.,MT. And Supervisor II : Musrifah Tohir, ST.,MT.the Outer Path Performance Analysis of Samarinda Balikpapan On Roads Soekarno Hatta At Km. 17 to KM.37. On the road Soekarno Hatta at kilometer 17 to 37 kilometers, the road conditions tend twisting - winding and around the side of the road there is a settlement there are not so dense.The intent of this research is to improve the quality and efficiency of road traffic movements outside the city, while the purpose of this study was to determine the performance of these roads and determine the category of service level indicators.Performance Analysis of the results of Roads Roads in Soekarno Hatta At Km. 17 to KM.37 on Sunday with average conditions obtained Vehicle Flow (Q) in the first segment is 731 veh / h and the second segment is 726 veh / h. Capacity (C) in the segment I & II is 2593.5 smp / h, Degree of Saturation (DS) in the first segment is the segment II was 0.281 and 0.279, Side Constraints on the first segment is 80 (L) is low and the second segment 56 (L ) is low, and Speed Travel Time on the first segment is 59.1 km / h and takes about 6.1 seconds, and the second segment is 60.2 km / h with a travel time of 5.9 seconds, while based on Service Level (Level Of Service) in the first segment is 0.281 and the second segment is 0.279 of calculations obtained a Service Level Indicator or <0.60 it can be concluded that the free flow, low volume, high speed, and the driver can select the desired speed.